Proposed Growth Strategy for PT Lintas Mitra Sejahtera (The Indonesian Journal of Business Administration, 2021)
The event organizer industry has grown by about 15% to 20% and the industry value is over Rp500 trillion. To date, there are approximately 4,000 business actors and approximately 40,000 regular employees. PT Lintas Mitra Sejahtera has been in the event organizer industry for nearly 23 years. Of course, we need to make changes and adaptations to the developments that have occurred so far. The purpose of this study is to analyze the internal conditions to determine the best way to strategy from the problem arising from the external conditions resulting from the rapid development of the Indonesian event organizer industry. And to know the components that influence the strategy to maintain the company's wheels and maintain its presence in the industry.The analysis was performed using several working frameworks with complementary results to obtain answers and solutions to the business problems faced by PT Lintas Mitra Sejahtera. The frameworks used include Five Forces Porter, PEST, VRIO, IFAS & EFAS, Grand Strategy Matrix, TOWS Matrix. Researchers use corporate data and questionnaire to obtain the right analytical components to generate accurate analytical results for the condition in which PT Lintas Mitra Sejahtera faces. The results of this study show that PT Lintas Mitra Sejahtera needs to focus on the three service product programs that are most in demand by users. As a result, PT Lintas Mitra Sejahtera can make internal improvements to the company which aims to support the development of these three programs in the short term and the long term development of the company in the event organizer industry which continues to growing rapidly. Keywords: PT Lintas Mitra Sejahtera, Event Organizer, VRIO, IFAS, EFAS, Growth Strategy